ANALYSYS OF PUBLIC VALUE IN THE ENTREPRENEURSHIP TRAINING PROGRAM AT LAPAS KELAS IIA BOJONEGORO - Rembran Mardika Resepta Naba; Esa Septian; Sri Kasiami (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2026)
-